Teacher Education in Times of Disruption: Teaching and Learning in Australian Universities During a Pandemic (Comparative & International Education Series, 2021)
Whilst higher education institutions in Australia are frequently subjected to systemic change, the ramifications of the COVID-19 pandemic have posed an unprecedented threat to their functionality, requiring them to completely and quickly adapt existing structures. With traditional models of tertiary education no longer a viable option, this case study sought to understand how teacher education within Australian HEIs has been reimagined in the online sphere as a result of the COVID-19 pandemic. Concurrently analysing three HEIs within the Australian state of New South Wales, and incorporating the perceptions of three respective teacher educators, this study considered how secondary English teacher education was informed and enacted during this unprecedented global crisis. This study subsequently demarcates the parameters of contemporary educational ideals, objectives for achieving quality teacher education, and the extent to which present models are viable and sustainable in achieving these goals for the foreseeable future. This study offers insight into the benefits and hindrances that have resulted from the COVID-19 pandemic and have consequently impacted teacher education in Australia during 2020. Ultimately, the findings highlight the importance for HEIs to remain malleable and relevant to a host of everchanging stakeholders and circumstances in order to provide quality teacher education, even during times of disruption.